Uma seqüência didática para aquisição/construção da noção de taxa de variação média de uma função - Silveira, Eugênio Cesar (2001)
The purpose of this work is to study the process by which students following a university-level course in the exact sciences acquire/construct the notion of average rate of change. An understanding of this notion could assist students in interpreting the meaning of the derivative as the average rate of change of a point. A didactic sequence was elaborated, inspired by Vergnaud (1994), who considers that the teaching and learning of mathematical notions and concepts should be approached by an exploration of problems, that is, by developing problem situations which favour new conceptualisations in their resolution. Eighteen pairs of students from a first year chemistry course worked on the sequence which lasted 1.440 minutes. The results indicated that the students advanced their understandings of average rate of change, as well as their ability to interpret graphs, for example, identifying intervals in which the function increases or decreases and describing the meaning of points where the function intersects the axes of the graph